History of leprosy treatment (Research, Society and Development, 2023)
Leprosy is a chronic, infectious, and slow-evolving disease caused by the bacterium Mycobacterium leprae, which mainly affects Schwann cells. Transmission mainly occurs through prolonged contact with undiagnosed and untreated patients. The objective of this research is to describe the history of leprosy, understand the different forms of treatment used over time, and evaluate the effectiveness of therapies used in each period. In addition, new techniques employed by pharmaceutical science in the treatment of leprosy will be explored. This study presents a descriptive and explanatory literature review that addresses the historical relevance of leprosy treatment. Works discussing the history of leprosy treatment, focusing on the evolution of therapeutic approaches throughout human history, were included in the analysis. The selected texts comprised publications from 2012 to 2022. Scientific articles not related to the history of leprosy treatment were excluded from this review. Leprosy is an infection with genetic components that contribute to susceptibility to the disease, which is considered complex, from initial infection by the bacterium to the clinical form in which it manifests in the individual. Although sciences have advanced in the study and treatment of leprosy and in the search for the eradication of the disease, it still maintains high infection rates and remains a major challenge for public health in Brazil.